Questions for Conversational Preaching - Voelz, Richard W. (Interpretation, 2021)
This essay considers the role of questions within sermons, in dialogue, with efforts to develop an ethos of conversational preaching. Questions reveal much about who preachers are, how they relate to listeners, and how they envision the homiletical situation. And in so doing, they continue to highlight the relationship between theology and rhetoric in preaching.